Case report: Acrodermatitis enteropathica result from a novel SLC39A4 gene mutation - Hua, Wenjing; Zou, Jialin; Zhuang, Yuan; Zhou, Taiguang (Frontiers in Pediatrics, 2022)
The clinical data and gene sequencing results in a child with acrodermatitis enteropathica were retrospectively reported, and the related literature was reviewed. A 9-year-4-month-old girl presented with repeatedly skin rash mainly distributed perioral, anogenital, and acral areas, accompanied with alopecia, and a low blood zinc level was found many times. A significant improvement was seen after continuous zinc supplementation. The genetic sequencing test demonstrated that the patient had compound heterozygous for two SLC39A4 mutations: c.1466dupT（p.S490Efs*155）and c.295G>A（p.A99T）, and her parents were heterozygous carriers of these two mutations. An improvement was achieved after continuous zinc supplementation. This case report might guide futher research on this aspect.